The Chinese Takings Law from a Comparative Perspective - Chenglin Liu (Washington University Journal of Law & Policy, 2008)
The objective of this Essay is to explore the correlations between the level of administrative costs and the likelihood of the abuse of eminent domain power. Part I traces the disparate treatment of private ownership of urban homes in China since 1949. It explains how and why the Chinese government dramatically changed its attitude towards private property due to varying ideological beliefs to which it subscribed at different times. Part II examines the serious problems detailed analysis of the three elements of the takings law: public purpose, compensation, and due process of law. Part III briefly analyzes the takings laws of the United States and Singapore in comparison to China, who is not alone in facing the tension between the protection of private ownership and the need for further economic development. The purpose of the comparative analysis is to provide new perspectives into the debate about how China’s takings law should be structured. This section also compares the administrative costs of takings among the three jurisdictions. Finally, the Essay concludes that, among other reasons, the extremely low administrative costs of the exercise of eminent domain in China have substantially contributed to a massive abuse of eminent domain power.
Keywords: Home ownership -- China; Eminent domain -- United States; Eminent domain -- China; Comparative law; Institutional economics; Due process of law; Eminent domain (Law); Public use; Regulatory taking (Law); China; Singapore; United States